Growth mindset, persistence, and self-efficacy in early adolescents: Associations with depression, anxiety, and externalising behaviours - Megan Cherewick; Emily Hipp; Prosper Njau; Ronald E. Dahl (Taylor & Francis Group, 2023)
Growth mindset, persistence, and self-efficacy are important protective factors in understanding adolescent psychopathology, including depression, anxiety, and externalising behaviours. Previous studies have shown that dimensions of self-efficacy (academic, social, and emotional) have differential protective effects with mental health outcomes and these differences vary by sex. This study examines the dimensional mediation of self-efficacy from motivational mindsets on anxiety, depression, and externalising behaviours in a sample of early adolescents ages 10-11. Surveys were administered to participants to measure growth mindset and persistence on internalising and externalising symptoms. The Self-Efficacy Questionnaire for Children (SEQ-C) was used to measure domains of self-efficacy for mediation analysis. Multi-group structural equation modelling by sex indicated that structural paths were not invariant by sex. Significant direct effects were identified from persistence to externalising behaviours in boys, and significant direct effects were identified from growth mindset to depression in girls. In a sample of Tanzanian early adolescents, self-efficacy mediates the protective association between motivational mindsets on psychopathology. Higher academic self-efficacy was associated with reduced externalising problems in both boys and girls. Implications for adolescent programmes and future research are discussed.